Histological characteristics, cell wall hydrolytic enzyme activity, and transcriptome analysis with seed shattering of Stylosanthes accessions - Li, Xinyong; Zhang, Jingwen; Zhang, Jingxue; Sheng, Wei; Huang, Rui; Dong, Rongshu; Ding, Xipeng; Liu, Pandao; Liu, Guodao (Frontiers in Plant Science, 2022)
Stylosanthes spp. (stylo) are annual or perennial legume forages that are widely grown as forage and cover crops in tropical and subtropical regions. However, the seed yield of stylo is very low due to serious seed shattering. In the present study, we found that, although seed shattering was common among the stylo accessions, the shattering rates were genetically different. Therefore, we first synthesized the morphological, histological characteristic, physiochemical, and transcriptome analyses to determine the seed shattering mechanism in stylo. In general, the stylo germplasm with shorter lobules and thicker stems had a lower seed shattering rate and a higher seed weight. The seed and seed stalk joint is the abscission zone in stylo. Multiplex histology and hydrolytic enzyme activity analysis showed that the tearing of the abscission zone occurs due to the intense enzymatic degradation of polygalacturonase and cellulase in the seed shattering-susceptible accession TF0275. cDNA libraries from the abscission zone tissues of TF0041 and TF0275 at 14, 21, and 28 days after flowering were constructed and sequenced. A total of 47,606 unigenes were annotated and 18,606 differentially expressed genes (DEGs) were detected, including 9,140 upregulated and 9,446 downregulated unigenes. Furthermore, the 26 candidate DEGs involved in lignin biosynthesis, cellulase synthesis, and plant hormone signal transduction were found at all three developmental stages. This study provides valuable insights for future mechanistic studies of seed shattering in stylo.